Manajemen Kegiatan Ektrakurikuler dalam Meningkatkan Mutu Sekolah Ditingkat SMP Kabupaten Bireuen - Nina Ayuni; Najmuddin Najmuddin; Iskandar Iskandar (Departement of Mathematics Education, 2025)
The purpose of this study is to analyze the management of extracurricular activities in improving the quality of schools at the SMP level in Bireuen Regency. The approach to this study uses a descriptive qualitative research method. Data collection techniques are observation, interviews and documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions/verification. The results of the study indicate that the planning of extracurricular activities initiated by the UPTD SMP Negeri Bireuen Regency has been implemented well with planning indicators carried out according to targets and objectives. The schedule, time, teacher supervisor and budget/cost of extracurricular activities are also systematically arranged according to the objectives of the extracurricular activity work program. In the organizational process at the UPTD SMP Negeri Bireuen Regency, several components are involved in the management of the extracurricular organizational structure which function to facilitate each division of tasks and train the responsibility of each member. The parties involved in the organizational process at the UPTD SMP Negeri Bireuen Regency are several people, namely the Principal, Vice Principal for Student Affairs, As for the implementation of extracurricular activities, it is held by the vice principal for student affairs under the supervision of the principal. The infrastructure to support the activities is complete and adequate so that in implementing it there are almost no obstacles. For supervisors, this can be in the form of evaluations carried out by various institutions, supervision of extracurricular activities at the UPTD SMP Negeri Bireuen Regency is carried out continuously and sustainably. Every week the supervising teacher submits a report to the extracurricular coordinator.